Thermodynamic properties of sodium aluminosilicate hydrate (N–A–S–H). Issue 39 (20th September 2021) - Walkley, Brant; Ke, Xinyuan; Hussein, Oday; Provis, John L.
Abstract : This study presents for the first time a systematic investigation of the thermodynamic properties of sodium aluminosilicate hydrate (N–A–S–H), through dissolution of pure synthetic N–A–S–H gels. Abstract : This study presents for the first time a systematic investigation of the thermodynamic properties of sodium aluminosilicate hydrate (N–A–S–H), through dissolution of pure synthetic N–A–S–H gels. Changes to the chemical composition and gel structure of N–A–S–H were determined via characterisation of the solid phase before and after dissolution by multinuclear solid state nuclear magnetic resonance spectroscopy, scanning electron microscopy coupled with energy dispersive X-ray spectroscopy, and X-ray diffraction measurements. The correlations between the bulk Si/Al ratio of the N–A–S–H phase and its thermodynamic properties were studied by characterisation of the aqueous phase and calculation of solubility constants. The solubility of synthetic N–A–S–H was compared with the solubility of metakaolin-based geopolymers with similar bulk Si/Al ratios. The solubility (log10   K sp ) of both the synthetic N–A–S–H gels and metakaolin-based geopolymers showed a close to linear correlation with the bulk Si/Al ratio of the phase. Lower solubility was observed for N–A–S–H gels and geopolymers with a higher bulk Si/Al ratio. This new insight is fundamental to understanding the physiochemical properties of geopolymers, and provides essential information for predicting their long-term stability and durability.